2013
DOI: 10.3329/bjn.v29i2.56175
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Common Risk Factors Associated with Carpal Tunnel Syndrome

Abstract: Objective: To identify the common risk factors associated with carpal tunnel syndrome. Methodology:This case-control observational study was conducted in the department of neurology and medicine, DMCH from May 2010 to April 2011 for a duration of 1 year. The study included purposively selected 80 persons. Patients attending the outdoor and admitted in indoor of department of neurology and medicine, DMCH with a clinically suspected CTS and established by electrophysiological parameters selected as cases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
0
1
Order By: Relevance
“…In contrast, the result of the present study is lower than the findings of the studies conducted among diabetic patients in the United Kingdom (20%), India (19.8%), Bangladesh (26%), and Ethiopia (29.2%)(28,37,46,47). Similarly, the prevalence of CTS in this study was much lower than the findings of the studies conducted in Saudi Arabia (81.7%) and Korea (71.2%)(9,48).…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast, the result of the present study is lower than the findings of the studies conducted among diabetic patients in the United Kingdom (20%), India (19.8%), Bangladesh (26%), and Ethiopia (29.2%)(28,37,46,47). Similarly, the prevalence of CTS in this study was much lower than the findings of the studies conducted in Saudi Arabia (81.7%) and Korea (71.2%)(9,48).…”
Section: Discussioncontrasting
confidence: 97%
“…The study showed that the mean age of the patients was about 60 years with the male-to-female ratio in both types of strokes being roughly 1:1 which correlates well with Haque et al's study. 5 Alam and associates 6 in a similar study reported that over one-third (36.2%) of the stroke patients were > 60 years old, which in the present study was around 45%. In another study…”
Section: Original Articlesupporting
confidence: 56%